PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS KOMPUTER MENGGUNAKAN FLIPBOOK MAKER DISERTAI NILAI ISLAM PADA MATERI PELUANG - Aris Munandar; Swaditya Rizki (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of developing Islamic value-based mathematics teaching materials is to produce teaching materials on Islamic value-based opportunity materials by using a valid and practical flipbook maker. This type of research is development refers to the development model in Sugiyono's opinion through 7 stages, potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. Based on the development of teaching materials research using this flipbook maker, the level of validity and practicality by conducting expert tests (material experts, design experts, Islamic value experts), responses from students. Material expert test obtained a percentage of 84% so that it was declared very feasible, the design expert test was obtained from 78% so that it was declared feasible, then the test of Islamic values experts obtained a percentage of 92% so it was declared very feasible. In the small group trial the percentage of 89% was obtained so that the media learning could be declared very practical. Based on the results of the study, it can be concluded that the learning media produced is very feasible, while the response of students to learning media is very practical. Mathematics teaching materials using flipbook makers are available to teach independent teaching materials and shape good characters and morals with the Islamic values listed as taught.